Satisfaction with childbirth care in Brazilian maternity hospitals participating in the Stork Network program: women's opinions - Yammê Ramos Portella Santos; Thaiza Dutra Gomes de Carvalho; Neide Pires Leal; Maria do Carmo Leal (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
This study aimed to describe maternal satisfaction with their experience during childbirth and birth and their association with sociodemographic, clinical and obstetric, and good practice characteristics during childbirth care. The sample included 2,069 women who wanted to express their opinions at the end of the interview of the Stork Network Assessment survey. Exploratory factor analysis was performed to summarize the variables of interest, creating latent variables, for input in the multiple logistic regression model. Six factors were created and tested in the model. Respect for the puerperal women was associated with satisfaction (vaginal delivery: 1.40; cesarean section: 1.47). Regarding those who underwent a cesarean section, satisfaction was associated with living in the Central-West (1.91) and South (2.00) regions and the presence of a companion during hospitalization (1.25). However, for women who had vaginal delivery, satisfaction was inversely associated with large hospitals (0.62) and undergoing interventions during labor and delivery (0.83), but positively with multiparity (1.98), receiving good care practices for labor and delivery (1.24), and having immediate contact with the newborn (1.20). The better understanding of the factors associated with mothers' care satisfaction for labor and delivery can improve care quality provided in public hospitals in the Brazil.